2014
DOI: 10.5185/amlett.2013.fdm.28
|View full text |Cite
|
Sign up to set email alerts
|

The Structural, Electrical And Magnetic Properties Of Perovskite (1-x)Ba(Fe1/2Nb1/2)O3–xBaTiO3 Ceramics

Abstract: Lead-free pseudo-binary compounds (1-x)Ba(Fe 1/2 Nb 1/2 )O 3 -xBaTiO 3 ; (0 ≤ x ≤ 1) have been synthesized at 1200C using conventional ceramic technique and characterized by X-ray diffraction, scanning electron microscopy, dielectric and vibration sample magnetometer studies. The crystal structure of the compounds is found to be monoclinic with the space group P2/m except for BaTiO 3 for which it is tetragonal (P4/mmm). The incorporation of BaTiO 3 significantly reduces the dielectric loss and improve the fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Besides, synthesis and superconducting properties of the (1 -x)YBa 2 Cu 3 O y -xBa(Y 1/2 Nb 1/2 )O 3 system have been studied by Vlakhov et al [19]. Furthermore, the electrical properties of a number of solid-solutions of Ba(Fe 1/2 Ta 1/2 )O 3 [9], Ba(Fe 1/2 Nb 1/2 )O 3 [20][21][22][23], Ba(Sm 1/2 Nb 1/2 )O 3 [24], Ba(Bi 1/2 Ta 1/2 )O 3 [25], Ba(Co 1/2 W 1/2 )O 3 [26], Ba(Zn 1/2 W 1/2 )O 3 [27], Bi 0.5 (Na 0.8 K 0.2 ) 0.5 TiO 3 -BiFeO 3 [28], Bi(Zn 0.5 Ti 0.5 )O 3 -BiFeO 3 [29], Bi(Mg 0.5 Zr 0.5 )O 3 -BiFeO 3 [30], with BaTiO 3 have been reported recently.…”
Section: Introductionmentioning
confidence: 97%
“…Besides, synthesis and superconducting properties of the (1 -x)YBa 2 Cu 3 O y -xBa(Y 1/2 Nb 1/2 )O 3 system have been studied by Vlakhov et al [19]. Furthermore, the electrical properties of a number of solid-solutions of Ba(Fe 1/2 Ta 1/2 )O 3 [9], Ba(Fe 1/2 Nb 1/2 )O 3 [20][21][22][23], Ba(Sm 1/2 Nb 1/2 )O 3 [24], Ba(Bi 1/2 Ta 1/2 )O 3 [25], Ba(Co 1/2 W 1/2 )O 3 [26], Ba(Zn 1/2 W 1/2 )O 3 [27], Bi 0.5 (Na 0.8 K 0.2 ) 0.5 TiO 3 -BiFeO 3 [28], Bi(Zn 0.5 Ti 0.5 )O 3 -BiFeO 3 [29], Bi(Mg 0.5 Zr 0.5 )O 3 -BiFeO 3 [30], with BaTiO 3 have been reported recently.…”
Section: Introductionmentioning
confidence: 97%
“…Bi doped BFN ceramics showed the dielectric relaxation properties and the giant dielectric constant response by the boundary-layer mechanism. Leadfree pseudo-binary compounds, (1-x)Ba(Fe 1/2 Nb 1/2 )O 3 -xBaTiO 3 (0 ≤ x ≤ 1), were studied by Bhagat et al [19]. They reported that the incorporation of BaTiO 3 significantly reduced the dielectric loss and improved the frequency and temperature stability of the dielectric properties of Ba(Fe 1/2 Nb 1/2 )O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, with the aim of getting lead-free compounds suitable for device application, attempts have been made to modify Ti-site by the pseudo-tetravalent cation (B,Nb) 4+ , where B is trivalent ion. Thus, the electrical properties of a number of solid-solutions, such as: Ba(Fe 0.5 Ta 0.5 )O 3 [8], Ba(Fe 0.5 Nb 0.5 )O 3 [16][17][18][19], Ba(Sm 0.5 Nb 0.5 )O 3 [20], Ba(Y 0.5 Nb 0.5 )O 3 [21], Ba(Bi 0.5 Ta 0.5 )O 3 [22], Ba(Co 0.5 W 0.5 )O 3 [23], Ba(Zn 0.5 W 0.5 )O 3 [24], with BaTiO 3 have been reported recently. Also, extensive literature survey suggested that no attempt has been made so far on (1-x) Ba(In 0.5 Nb 0.5 )O 3 -x BaTiO 3 (0 ≤ x ≤ 1) solid-solutions.…”
Section: Introductionmentioning
confidence: 99%